2019
DOI: 10.1101/2019.12.21.885988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NADPH diaphorase neuronal dystrophy in gracile nucleus, cuneatus nucleus and spinal trigeminal nucleus in aged rat

Abstract: NADPH -diaphorase (N-d) activity is commonly used to identify NOS-ergic neurons. In our previous study, Nd positive neuritic dystrophy and spheroid termed aging-related N-d Body is discovered in the lumbosacral spinal cord in the normal aging rats. Histological studies also reveal that N-d positive neurodegenerative changes occur in the gracile nucleus. We re-examined N-d activity in gracile nucleus in aged rat. We found Nd positive neuritic dystrophy and spheroid also occurred in the cuneatus nucleus and spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…11 Within a few months of spinal cord injury, NADPHdiphosphorase abnormality is seen in the nucleus cuneatus, nucleus gracilis, and spinal trigeminal tract of rats. 32 Neuropathic pain may be experienced by about 80% of individuals who sustain spinal cord injury. 22,56,57 Some studies have pointed out the role of dorsal root ganglion in neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…11 Within a few months of spinal cord injury, NADPHdiphosphorase abnormality is seen in the nucleus cuneatus, nucleus gracilis, and spinal trigeminal tract of rats. 32 Neuropathic pain may be experienced by about 80% of individuals who sustain spinal cord injury. 22,56,57 Some studies have pointed out the role of dorsal root ganglion in neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that any pathology in the spinal cord may cause hyperexcitability in the dorsal horn. [25,26] This might occur through dysregulation of glutamate release, uptake and receptor expression, [25,[27][28][29] dendritic spine remodeling, [30,31] loss of local inhibitory (GABAergic) tone, [32][33][34][35][36] descending (particularly serotonergic) inhibitory input to spinal nociceptive circuitry, [28,39,40] or increased expression of calcium channel subunit. [39] Within a few months of spinal cord injury, NADPH-diphosphorase abnormality is seen in the nucleus cunaetus, nucleus gracilis, and spinal trigeminal tract of rats.…”
Section: Discussionmentioning
confidence: 99%
“…[39] Within a few months of spinal cord injury, NADPH-diphosphorase abnormality is seen in the nucleus cunaetus, nucleus gracilis, and spinal trigeminal tract of rats. [40] Neuropathic pain may be experienced by about 80% of individuals who sustain spinal cord injury. [41][42][43] Some studies have pointed out the role of dorsal root ganglion in neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%